Traps, Troubles, And Triumphs In A Case Series Of Thyroid Cytology - Goel, Seema; Atri, Kanak; Sengar, Kangana; Gupta Devra, Anshu (Journal of Neonatal Surgery, 2025)
Background: Fine-needle aspiration cytology (FNAC) is a widely employed tool for evaluating thyroid lesions, giving high sensitivity and specificity. However, cytologic-histopathologic discordance can occur due to overlapping cytomorphologic features and interpretative challenges, likely affecting patient management. Methods: This case series presents three challenging cases of thyroid lesions where FNAC results were at variance with subsequent histopathologic diagnoses. Each case was examined for cytological features, sampling adequacy, radiologic correlation, and clinical findings to identify sources of diagnostic discrepancies. Results: Case 1 involved a thyroid nodule diagnosed as benign on FNAC but later confirmed as papillary thyroid carcinoma on histopathology. Case 2 presented as a benign colloid nodule with cystic changes, which histopathologic examination revealed as follicular variant of papillary thyroid carcinoma. Case 3 was initially classified as suspicious for malignancy on FNAC but was confirmed as a benign adenomatous nodule postoperatively. The discordance in these cases resulted from overlapping cytological features, inadequate sampling, and interpretative variability. Conclusion: FNAC remains an important first-line diagnostic modality for thyroid lesions; however, cytologic-histopathologic discrepancy highlights the limitations of relying solely on cytology. A multimodal approach including clinical correlation, radiologic evaluation, and, when necessary, repeat FNAC or molecular testing can improve analytical accuracy. Cognizance of potential pitfalls in cytological interpretation is essential to reduce errors and enhance patient management